2014
DOI: 10.2967/jnumed.113.136143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 18F-UCB-H as a Novel PET Tracer for Synaptic Vesicle Protein 2A in the Brain

Abstract: Synaptic vesicle protein 2 isoforms are critical for proper nervous system function and are involved in vesicle trafficking. The synaptic vesicle protein 2A (SV2A) isoform has been identified as the binding site of the antiepileptic levetiracetam (LEV), making it an interesting therapeutic target for epilepsy. 18 F-UCB-H is a novel PET imaging agent with a nanomolar affinity for human SV2A. Methods: Preclinical PET studies were performed with isoflurane-anesthetized rats. The arterial input function was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 26 publications
9
79
0
Order By: Relevance
“…These results were confirmed by in vitro autoradiography using the 18 F-UCB-H radioligand. This radiotracer has been shown to specifically bind to the SV2A protein [15, 16]. Autoradiograms obtained post-incubation using a constant radiotracer concentration enabled us to visualize decreased binding of 18 F-UCB-H in all hippocampus regions of the Grik4:SV2A-cKO animals compared to WT littermates (***: p <0.001) (Fig 3C and 3D).…”
Section: Resultsmentioning
confidence: 96%
“…These results were confirmed by in vitro autoradiography using the 18 F-UCB-H radioligand. This radiotracer has been shown to specifically bind to the SV2A protein [15, 16]. Autoradiograms obtained post-incubation using a constant radiotracer concentration enabled us to visualize decreased binding of 18 F-UCB-H in all hippocampus regions of the Grik4:SV2A-cKO animals compared to WT littermates (***: p <0.001) (Fig 3C and 3D).…”
Section: Resultsmentioning
confidence: 96%
“…Recently, [ 18 F]UCB-H, a high-affinity PET ligand for SV2A, was developed [73, 74]. This tracer shows a nanomolar affinity for SV2A in the brain, which has been demonstrated using µPET in a preclinical study by Warnock et al [75] in the rat brain. After a single intravenous administration in rats, [ 18 F]UCB-H showed rapid and high-level brain uptake, with a free brain-to-plasma ratio of greater than 1 at 5, 10, and 20 min after administration.…”
Section: The Role Of Sv2a In Modulating Neuronal Excitability In the mentioning
confidence: 99%
“…In addition to their potential value in the study of epilepsy, SV2A PET tracers could be of interest as useful tools to measure synaptic density in humans [55, 75]. SV2A does not appear to affect vesicle formation as synaptic morphology and vesicle density were not altered in SV2A knockout animals [34, 36].…”
Section: The Role Of Sv2a In Modulating Neuronal Excitability In the mentioning
confidence: 99%
See 1 more Smart Citation
“…UCB-A has been radiolabeled with 11 C and tested in mini-pigs (12), rats (13), and rhesus monkeys (Nabulsi et al, unpublished data, 2012) but showed slow kinetics (prolonged retention in brain tissue) and may therefore not be suitable for PET imaging (unpublished data). UCB-H was radiolabeled with 18 F and displayed good kinetics in rats (14) and nonhuman primates (15) and acceptable dosimetry in humans (16); however, its radiosynthesis has proven challenging and specific binding was relatively low. In this study, we report the radiosynthesis and characterization of 11 C-UCB-J as a best-in-class SV2A PET tracer.…”
mentioning
confidence: 99%